Analysis of Water Quality of a Lentic Water Reservoir of Arrah, Bihar (India) by Application of the Water Quality Index (WQI) - Gupta, Anjali (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The water quality index (WQI) is a dimensionless number using arbitrary grading curves to normalize values by combining various characteristics of water quality water into a single value. It has been utilized traditionally to evaluate the water quality for rivers, streams, lakes, and other water sources. So the purpose of the current investigation is to evaluate the WQI of a lentic water body in Arrah (Bihar). For the three seasons' WQI calculations i.e. Monsoon, winter and summer, physico-chemical variables were tracked. For calculating WQI ten physico-chemical parameters were recorded. pH ranges between 7.54-7.86, total alkalinity from 112-167, total hardness 70-160, TDS 325-487, Calcium 43-67, Magnesium 26-130, Chloride 30-52, Sulphate 16-36, DO 5.2-5.7 and Nitrate from 21-34. The permitted levels were met for the variables total hardness, pH, TDS, Calcium, Dissolved Oxygen, Chloride, Nitrate and Sulphate. On the other hand, the values of total alkalinity were higher in the winter and summer seasons, and the value of magnesium in the summer season was higher than prescribed by Indian Standards.